The ancient settlement of Piammiano‐Statonia (Bomarzo, Italy): New data from 2D and 3D electrical tomography. Issue 2 (21st December 2020) - Leucci, Giovanni; De Giorgi, Lara; Ditaranto, Immacolata; Miccoli, Ilaria; Scardozzi, Giuseppe
Abstract: This study presents new archaeological data concerning the ancient layout of Piammiano, an Etruscan and Roman settlement located in the Tiberine internal Etruria (probably corresponding to the ancient town of Statonia ), still little known. These data have been obtained by geophysical surveys performed using the Electrical Resistivity Tomography technique. These investigations were carried out in the central sector of the plateau where the settlement lies, and they have documented the presence of ancient buried structures at a depth of between about 0.5 and 2.5 m. These structures has the same orientation of the main road of the ancient settlement, and they are also consistent with the orientation of the structures documented in previous geophysical surveys and archaeological excavations carried out in the westernmost sector of the investigated area. Specifically, the new geophysical surveys have highlighted the presence of the buried remains of the road and numerous walls, some of which are pertaining to a large building with porticoes on the two sides overlooking the Tiber valley. Furthermore, a channel network perhaps linked to a cistern was documented at more depth.